SUPER CONNECTED DOMINATION IN GRAPHS - Enriquez, Enrico Limbo; Fedellaga, Bea Elaine Parrilla; Loquias, Carmelita M.; Estrada, Grace M.; Baterna, Margie L. (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
In this paper, we initiate the study of super connected dominating set of a graph  by giving the super connected domination number of some special graphs. Further, we shows that given positive integers  and  such that  and  there exists a connected graph  with ,  and .  Finally, we characterize the super connected dominating set of the join, corona, and Cartesian product of two graphs.